2010
DOI: 10.1177/1742395310364253
|View full text |Cite
|
Sign up to set email alerts
|

Bringing smoking cessation to diabetes clinics in Indonesia

Abstract: This study demonstrates the feasibility of disease-centred doctors' messages about smoking cessation for patients with diabetes, supported by the presence of a CC motivating clinicians to routinely give patients cessation messages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 17 publications
2
44
0
Order By: Relevance
“…Table 2 compares characteristics among patients in intervention and control groups. Both groups showed similar characteristics regarding mean age at smoking initiation (17.6 [6.2] vs. 17.9 [6.0], p = 0.518), median (Q1-Q3) number of cigarettes smoked daily in the last 2 weeks (16.5 [8][9][10][11][12][13][14][15][16][17][18][19][20] vs. 15 [10][11][12][13][14][15][16][17][18][19][20], p = 0.531). Education level, comorbidities, diabetesrelated complications, duration of diabetes, and previous attempts to quit smoking were similar in the two groups.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Table 2 compares characteristics among patients in intervention and control groups. Both groups showed similar characteristics regarding mean age at smoking initiation (17.6 [6.2] vs. 17.9 [6.0], p = 0.518), median (Q1-Q3) number of cigarettes smoked daily in the last 2 weeks (16.5 [8][9][10][11][12][13][14][15][16][17][18][19][20] vs. 15 [10][11][12][13][14][15][16][17][18][19][20], p = 0.531). Education level, comorbidities, diabetesrelated complications, duration of diabetes, and previous attempts to quit smoking were similar in the two groups.…”
Section: Resultsmentioning
confidence: 90%
“…However, systematic interventions to help diabetic patients stop smoking are difficult since many are not motivated to quit [13]. Also, the number of studies assessing the effectiveness of diabetic-specific smoking cessation programs is low [14][15][16], particularly in primary care [17,18], despite diabetic patients visiting their family physicians periodically for routine check-ups. According to the World Health Organization [19], the optimal level of service delivery should be based on a diabetes team comprised of a physician and a professional educator in the primary care setting.…”
Section: Introductionmentioning
confidence: 98%
“…However, although no smokers quit smoking, the influence of screening could be interpreted through participants' engagement in harm-reduction behaviors. Harm reduction was illustrated by participants' reducing their daily smoking, which may be perceived as a safer way to smoke among smokers undergoing cessation interventions (Ng et al, 2010;Nichter, 2003). This harm-reduction behavior was also reported in a recent study conducted at the Mayo Clinic that found that smokers decreased their daily smoking rate by approximately five cigarettes in the year following lung screening (Shi & Iguchi, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…36 Smoking cessation interventions also have been shown to improve behavior outcomes among people with diabetes. 37,38 Diabetes educators can select from a wide range of approaches to deliver educational interventions. Targeting the strategy or combination of strategies to the patient's age, needs, preferences, literacy, and situation will ensure an individualized approach that promotes adherence and enhances effectiveness.…”
Section: Effective Interventions and Strategies To Reduce Risksmentioning
confidence: 99%